2006
DOI: 10.1007/bf03022508
|View full text |Cite
|
Sign up to set email alerts
|

Non-invasive ventilation corrects alveolar hypoventilation during spinal anesthesia

Abstract: Purpose: To document and explain the beneficial effects of non-invasive ventilation in correcting hypoxemia and hypoventilation in severe chronic obstructive pulmonary disease, during spinal anesthesia in the lithotomy position. Clinical features:A morbidly obese patient with severe chronic obstructive pulmonary disease underwent prostate surgery in the lithotomy position under spinal anesthesia. Hypoxemia was encountered during surgery, and a profound decrease of forced vital capacity associated with alveolar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 16 publications
1
11
0
Order By: Relevance
“…Indeed, in PSV, the tidal volume achieved depends on the patient's own effort added to that of the ventilator's inspiratory pressure. In this mode, an improvement in diaphragmatic ventilator excursion has been reported by ultrasonography [14]. We observed that the dependent lung in lateral decubitus position received significantly more ventilation than the nondependent lung in awake patients during SB.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…Indeed, in PSV, the tidal volume achieved depends on the patient's own effort added to that of the ventilator's inspiratory pressure. In this mode, an improvement in diaphragmatic ventilator excursion has been reported by ultrasonography [14]. We observed that the dependent lung in lateral decubitus position received significantly more ventilation than the nondependent lung in awake patients during SB.…”
Section: Discussionmentioning
confidence: 53%
“…PSV is a ventilator mode recently available in anesthesia ventilators. Use of NIV in anesthesia has been reported during the preoxygenation phase in obese patients to enhance oxygenation before intubation [8,9] and also in the intraoperative period in 3 settings [10]: therapeutic to treat an established perioperative acute respiratory failure, prophylactic in patients with chronic severe respiratory limitations, and prophylactic in sedated healthy patients to avoid hypoventilation due to anesthesia [11][12][13][14][15][16][17][18]. Effects of spontaneous breathing during general anesthesia were assessed by comparing the ventilation distribution in 30 nonobese patients enrolled in a randomized trial [19].…”
Section: Introductionmentioning
confidence: 99%
“…Our experience combined with evidence from published case reports of the combination of non-invasive lung ventilation and regional anaesthesia techniques [8][9][10][11][12] suggests that even critically ill patients may successfully undergo major abdominal and thoracic surgery in this manner. In this case we used BiPAP, since the increased inspiratory pressure aids lung inflation while the positive expiratory pressure prevents alveolar collapse [1].…”
Section: Discussionmentioning
confidence: 84%
“…However, in critically ill patients, some elements of VATS procedures are likely to increase the chances of acute ventilatory failure. These include the lateral position, the iatrogenic pneumothorax and the duration of the operation, often in excess of 1 h. Non-invasive methods of mechanical lung ventilation may minimise the incidence of respiratory complications while allowing effective lung ventilation [7], and these methods have been used to assist spontaneous lung ventilation during abdominal surgery [8][9][10][11][12]. We describe the use of non-invasive ventilation during thoracic surgery.…”
mentioning
confidence: 99%
“…Although these patients pose substantial challenges to the anaesthetist, based on this preliminary experience, we think that critically ill patients scheduled for palliative surgery can be successfully managed with the combination of minimally invasive surgical techniques, neuraxial block and NIV. Our unpublished experience combined with evidence from published case reports of the combination of NIV and regional anaesthesia techniques [67][68][69][70][71] suggests that even critically ill patients may successfully undergo major abdominal and thoracic surgery in this manner.…”
Section: Interventional Cardiologymentioning
confidence: 99%